2021
DOI: 10.3390/ijms22052478
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Sensing Receptor (CaSR), Its Impact on Inflammation and the Consequences on Cardiovascular Health

Abstract: The calcium Sensing Receptor (CaSR) is a cell surface receptor belonging to the family of G-protein coupled receptors. CaSR is mainly expressed by parathyroid glands, kidneys, bone, skin, adipose tissue, the gut, the nervous system, and the cardiovascular system. The receptor, as its name implies is involved in sensing calcium fluctuations in the extracellular matrix of cells, thereby having a major impact on the mineral homeostasis in humans. Besides calcium ions, the receptor is also activated by other di- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 108 publications
1
32
0
2
Order By: Relevance
“…Astaxanthin: to protect neurons from oxidative stress [9]. Calcium lactate and calcium carbonate: to make calcium available to the CaSRs in the GI tract [10].…”
Section: Methodsmentioning
confidence: 99%
“…Astaxanthin: to protect neurons from oxidative stress [9]. Calcium lactate and calcium carbonate: to make calcium available to the CaSRs in the GI tract [10].…”
Section: Methodsmentioning
confidence: 99%
“…CaSR is a seven-transmembrane-domain receptor, belonging to the family of G-proteincoupled receptors [66]. It is expressed in several organs, including vascular cells [67,68]. It senses extracellular levels of multivalent ions, polyamines, and polypeptides as well as aminoglycoside antibiotics [66,68].…”
Section: Calcium-sensing Receptor (Casr)mentioning
confidence: 99%
“…It is expressed in several organs, including vascular cells [67,68]. It senses extracellular levels of multivalent ions, polyamines, and polypeptides as well as aminoglycoside antibiotics [66,68]. It also activates intracellular signaling pathways for cellular proliferation and differentiation.…”
Section: Calcium-sensing Receptor (Casr)mentioning
confidence: 99%
“…Studies of CaSR mutations, which cause disorders of calcium homeostasis, showed. G-protein independent signaling [ 393 ]. Functional assessment of these mutations demonstrated the importance of the homodimer interface and transmembrane domain in biased signaling.…”
Section: Amino Acid Metabolitesmentioning
confidence: 99%
“…CaSR is expressed on immune cells, such as monocytes, macrophages, proerythroblasts, erythroblasts, and megakaryocytes [ 393 ]. CaSR is also expressed by T lymphocytes, although not by B lymphocytes [ 406 ].…”
Section: Amino Acid Metabolitesmentioning
confidence: 99%